Using thermal annealing and salt remelting to increase tensile properties of 3D FDM prints. (February 2022) - Szust, Agnieszka; Adamski, Grzegorz
Highlights: The thermal annealing process conducted at the temperature of 60 °C. for 1 h results in 24% increase in strength of FDM PLA parts. The tensile strength of PETg FDM parts measured in Z direction increases over 300% after salt remelting. The precision of the parts remains high after the salt remelting process. Abstract: Addtive Manufacturing techniques such as FDM (Fused Deposition Modeling) are becoming more significant in prototyping and have potential to be used in low-volume production, which generates the need of better tensile properties of FDM printed parts. The effects of process parameters (printing orientation and layer height), thermal annealing process and salt remelting process on tensile properties and anisotrophy of the FDM parts was examined. The tensile strength of PETg FDM parts measured in Z direction increases over 300% after salt remelting process and the anisotrophy of the parts becomes negligible.